The determinants of international students studying in China: An empirical research based on the “Belt and Road” perspective - Li, Tingsong; Zong, Xiaohua; Zhang, Wei (PLOS ONE, 2025)
This paper explores the factors influencing international students’ decisions to study in China, based on data from 2003 to 2018. Using a two-way fixed effect model and a comprehensive theoretical framework that integrates push-pull theory, human capital theory, and proximity theory, the study investigates the roles of economic, educational, national stability, and sociocultural determinants. The findings reveal that economic factors, particularly the trade relations between the home country and China, play a significant role in attracting international students. National stability, the number of Confucius Institutes, and language similarity also emerge as key influences. Moreover, educational factors such as Chinese university rankings and scholarships are crucial in drawing students. The study further shows that international students from B&R countries are more sensitive to economic and sociocultural factors than those from non-B&R countries. Postgraduate students are more focused on China’s economic development and educational strength, while undergraduates prioritize national stability and sociocultural aspects. These findings offer insights for policymakers and higher education institutions, providing strategic recommendations to effectively attract and support international students in a rapidly changing global landscape.